Parental behavior, adult attachment, and DNA methylation of the MT2 oxytocin receptor gene region – The moderating role of neuroticism - Laura Geißert; Juergen Hennig (PLoS ONE, 2026)
Parental behavior, especially in childhood, affects the child’s development in numerous ways. Over the last decade, the aim to get a deeper understanding of how early experiences influence behavior later in life has led to an increased popularity of epigenetic studies. Several studies focused on negative childhood experiences, increased methylation at different oxytocin receptor gene sites, and deficits in social behavior in adolescence or adulthood. The current study focused on the role of parental behavior, personality, and methylation of the MT2 region in the oxytocin receptor gene on insecure attachment styles in young adulthood. A total number of N = 71 students (55 females, one non-binary) completed an online survey and provided cell material (buccal cell swaps) for methylation analysis. Parental behavior was measured with the Parental Bonding Instrument (PBI), personality with the NEO Five-Factor Inventory (NEO-FFI), and adult attachment with the Attachment Style Questionnaire (ASQ). Results showed a moderating effect of neuroticism on the relation between maternal care and methylation of the MT2 region: higher maternal care was associated with lower methylation levels but only among participants with low neuroticism scores. No association of methylation with anxious or avoidant attachment was observed and no effect of paternal care at all. The results emphasize the model of early environmental influences on behavior in respect to changing gene activity and will be discussed with respect to the MT2 region and early life experiences on the one, and the association with personality on the other hand.